PENGEMBANGAN LKPD INQUIRY BASED LEARNING UNTUK MENDUKUNG KEMAMPUAN PENALARAN DAN PEMBUKTIAN MATEMATIS - Mohamad Waluyo; Wahyuning Putri Bima (Prodi Pendidikan Matematika Universitas Pesantren Tinggi Darul Ulum Jombang, 2023)
This study aims to develop valid, practical, and effective inquiry-based learning worksheets to support students' mathematical reasoning and proving abilities in the matter of a system of two-variable linear equations (SPLDV). This study adopts the ADDIE development model. Methods of data collection through interviews, questionnaires, and tests. The subjects of this study were students of class VIII E as the experimental class and students of class VIII B as the control class. The results of the validity assessment obtained a percentage of 85% with the very valid category, the practicality assessment obtained a percentage of 86% with the very practical category, and the effectiveness assessment obtained a percentage of 58% with the category quite effective, and there was a significant difference between students' reasoning abilities and mathematical proving experimental class with control class.